DIGITALIZATION IN EDUCATION: OPPORTUNITIES AND CHALLENGES (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
The article analyzes the process of digitalization in the education system, exploring its opportunities and existing challenges. Recommendations are also provided to enhance the effectiveness of digital learning and overcome limitations.